2022
DOI: 10.3389/fpls.2022.885694
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of AP2/ERF gene family in the desert legume Eremosparton songoricum: Identification, classification, evolution, and expression profiling under drought stress

Abstract: Eremosparton songoricum (Litv.) Vass. is a rare leafless legume shrub endemic to central Asia which grows on bare sand. It shows extreme drought tolerance and is being developed as a model organism for investigating morphological, physiological, and molecular adaptations to harsh desert environments. APETALA2/Ethylene Responsive Factor (AP2/ERF) is a large plant transcription factor family that plays important roles in plant responses to various biotic and abiotic stresses and has been extensively studied in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
2
1
0
Order By: Relevance
“…Consistent with AtRAP2.6L (Gao et al, 2020), MdERF113 is also localized in the nucleus when transiently expressed in epidermal cells of N. benthamiana . According to our findings and the results of previous articles, MdERF113 functions as a member of the ERF/AP2 TF family (Han et al, 2022; Xie et al, 2019; M. Zhao et al, 2022). Further bioinformatic analysis revealed that MdERF113 and AtRAP2.6L share a conserved AP2 structural domain (Figure 2B), which belonged to the AP2/ERF family.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with AtRAP2.6L (Gao et al, 2020), MdERF113 is also localized in the nucleus when transiently expressed in epidermal cells of N. benthamiana . According to our findings and the results of previous articles, MdERF113 functions as a member of the ERF/AP2 TF family (Han et al, 2022; Xie et al, 2019; M. Zhao et al, 2022). Further bioinformatic analysis revealed that MdERF113 and AtRAP2.6L share a conserved AP2 structural domain (Figure 2B), which belonged to the AP2/ERF family.…”
Section: Discussionsupporting
confidence: 87%
“…MdERF113 is also localized in the nucleus when transiently expressed in epidermal cells of N. benthamiana. According to our findings and the results of previous articles, MdERF113 functions as a member of the ERF/AP2 TF family (Han et al, 2022;Xie et al, 2019;M. Zhao et al, 2022).…”
supporting
confidence: 86%
“…Further division of the ERF family can be performed based on the DNAbinding domain, resulting in the ERF and DREB subfamilies [23]. The Soloist subfamily stands out due to substantial differences in its protein sequence characteristics and specific gene structures, warranting its classification as a distinct subfamily within the AP2/ERF family [24].…”
Section: Introductionmentioning
confidence: 99%
“…The ERF family is divided into ERF and Dehydration-Responsive Element Binding (DREB) subfamilies according to cis-acting elements associated with ERF binding; ERF subfamily members bind to the ethylene response element GCC-box, while DREB subfamily members bind to the drought and low temperature response element DRE [ 11 ]. The RAV family is characterized by a conserved AP2/ERF domain at the N-terminus and a B3 domain at the C-terminus [ 12 ], while the soloist family contains an AP2/ERF conserved domain, but its gene structure is significantly different from that of other subfamilies [ 13 ]. AP2/ERF family members are important transcription factors in plants, and their functions cannot be replaced.…”
Section: Introductionmentioning
confidence: 99%